(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Low birth weight (LBW) neonates remain highly vulnerable to hypothermia, sepsis, feeding difficulties, poor weight gain, and neonatal mortality. Kangaroo Mother Care (KMC), involving skin-to-skin contact and exclusive breastfeeding support, has emerged as a cost-effective intervention for improving neonatal outcomes. Aim: To compare the effectiveness of Kangaroo Mother Care versus conventional care in low birth weight neonates admitted to the neonatal unit. Materials and Methods: This prospective comparative study was conducted in the Department of Pediatrics, Mahaveer Institute of Medical Sciences and Research, Bhopal, over a period of six months from November 2025 to April 2026. A total of 240 low birth weight neonates were included and divided equally into two groups: KMC group (n=120) and conventional care group (n=120). Parameters including weight gain, duration of hospital stay, breastfeeding rates, hypothermia episodes, sepsis incidence, and mortality were compared. Statistical analysis was performed using SPSS software version 25.0. Results: Neonates receiving Kangaroo Mother Care demonstrated significantly higher daily weight gain, earlier initiation of exclusive breastfeeding, reduced hypothermia episodes, shorter hospital stay, and lower incidence of neonatal sepsis compared to conventional care. Mortality rate was also lower in the KMC group. Conclusion: Kangaroo Mother Care significantly improves clinical outcomes among low birth weight neonates and should be promoted as an effective, economical, and feasible neonatal care strategy in resource-limited settings.